Meteorological observations at Syowa Station in 2002 by the 43rd Japanese Antarctic Research Expedition - Nobuhiko Kizu; Shin Kanehama; Hirotsugu Kamata; Keisuke Ueno; Katsue Nagai (Antarctic Record, 2007)
This report describes the result of meteorological observations at Syowa Station and neighboring areas from February 1, 2002 to January 31, 2003, carried out by the Meteorological Observation Team of the 43rd Japanese Antarctic Research Expedition (JARE-43). Instruments and methods for compiling data were almost the same as those used in the 42nd Expedition. Remarkable weather phenomena observed during the period were as follows.1) In the surface weather observations, air temperature was higher than in a normal year from May to October. In addition, a blizzard (Class A), observed in the middle of September, recorded 57.9m/s (maximum instantaneous wind velocity) and 45.4m/s (maximum 10 minutes average wind velocity). These wind speed were the maximum values ever observed in September and third rank in any month.2) In aerological observations, sudden warming in the lower stratosphere appeared earlier (beginning of July), and major warming with vortex split which was the first observation in the Southern Hemisphere occurred in late September.3) The ozone hole was observed from the beginning of August to the middle of October. After late October, the total ozone amount was higher than the average of the last 20 years.